Model Kolaboratif untuk Pengembangan UMKM: Kegiatan Gathering Kewirausahaan sebagai Upaya Bersama Mahasiswa Magang dan Pengusaha Lokal - Septianingsih, Ika Rahma; Faridatussalam, Sitti Retno (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This article examines the role of gathering activities as an interactive platform for exchanging ideas, knowledge, and skills between students and local entrepreneurs. Through the Independent Entrepreneurship program, students bring academic expertise and offer new perspectives to address challenges faced by MSMEs. Conversely, local entrepreneurs provide valuable practical experience and industry insights, enriching students' learning with real-world contexts. The interaction between these parties strengthens professional networks and fosters mutually beneficial experiential learning. Students have the opportunity to apply theoretical knowledge in real case studies, while MSMEs can adopt more effective and innovative business strategies, such as enhancing digital marketing and operational efficiency. This entrepreneurship gathering program is expected to increase students' job readiness and establish a collaborative model that can be replicated in various regions to support local economic development. Therefore, this article recommends the strengthening and expansion of this program to achieve broader and more sustainable impacts.